Veränderung der Struktur elementarer Schnelligkeitsleistungen im Altersgang - Kurth-Rosenkranz, R. (Leipziger Sportwissenschaftliche Beiträge, 2016)
The elementary motor speed is considered as a theoretical construct, which is primarily used in the German-speaking world. The 4-dimensional construct has so far not been proved by empirical data. The following article will examine whether the collected data from three age cohorts can be structured according to the conceptions of the construct by factor analysis. The results show a differentiation and stabilization from the child age to the adult age from a nonspecific speed to a factor structure corresponding to the theoretical construct.